Marital and family biographies considered in the perspective of self-creation to parenthood - Dubas, Elżbieta; Wąsiński, Arkadiusz; Słowik, Aneta; Agnieszka Gralak; Hrehorowicz, Uta; Demkowicz, Leszek (Biografie rodzinne i uczenie się: Tom 8, 2021)
The article discusses the specificity of coexistence and mutual relations between several meaningful categories: parenthood, self-creation and biography. These reflections take place in several planes oriented at capturing the essence: a) parenthood recognized as a process of realization of the dynamic value of accompanying a child, b) self-creation included in the lifelong plan of personal development of an adult in the context of his aspiration to be and become a parent, c) the integral nature of the relationship between individual and collective (community) biography and adult self-creation taking place in the space of married and family community, d) the biographical dimension of self-creation to biological and adoptive parenthood.The aim of the article is to present the arguments justifying the thesis that these categories not only coexist, but in practice coexist in specific relationships. The biographical work of spouses and other family members considered on an individual level maintains a symbolic link with marital and family biographies. The self-creation of spouses takes place on the basis of their self-reflexive reference to their own biography oriented prospectively. Finally, parenthood, considered as the process of reaching maturity as a parent in the multi-faceted companionship of a child, can be realized on the basis of their personal self-creation to parenthood.